Walt Disney's The jungle book : adapted from the Mowgli stories by Rudyard Kipling - Kipling, Rudyard, 1865-1936.; Walt Disney Productions (Maitland, FL Advance Publishers, L.C., 2006)
The animal friends of the boy raised by wolves escort him out of the jungle to keep him safe from the tiger who seeks to kill him
Keywords: Animals -- Fiction; Jungles -- Fiction